2021
DOI: 10.1186/s13046-021-01988-6
|View full text |Cite
|
Sign up to set email alerts
|

Glycoproteomics identifies HOMER3 as a potentially targetable biomarker triggered by hypoxia and glucose deprivation in bladder cancer

Abstract: Background Muscle invasive bladder cancer (MIBC) remains amongst the deadliest genitourinary malignancies due to treatment failure and extensive molecular heterogeneity, delaying effective targeted therapeutics. Hypoxia and nutrient deprivation, oversialylation and O-glycans shortening are salient features of aggressive tumours, creating cell surface glycoproteome fingerprints with theranostics potential. Methods A glycomics guided glycoproteomics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 50 publications
(107 reference statements)
1
35
0
Order By: Relevance
“…In particular, the highly hypoxic muscle-invasive bladder cancer (MIBC) overexpresses the cancer-associated carbohydrate antigen sialyl-Tn (STn), which has been reported to be at least in part due to a HIF-1α-dependent cell survival strategy that favors cell migration and invasion ( 133 ). Recently, through the application of glycoproteomics in bladder cancer, the same group demonstrated cell surface expression of an ordinarily intracellular protein, homer homolog 3 (HOMER3), carrying short-chain O-glycans that are characteristic of membrane proteins ( 134 ). They further reported that under glucose deprivation and hypoxic conditions, HOMER3 contributed to the tumor cell’s invasive capacity.…”
Section: Hypoxia-driven Tumor Plasticity and Heterogeneity Incite Imm...mentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the highly hypoxic muscle-invasive bladder cancer (MIBC) overexpresses the cancer-associated carbohydrate antigen sialyl-Tn (STn), which has been reported to be at least in part due to a HIF-1α-dependent cell survival strategy that favors cell migration and invasion ( 133 ). Recently, through the application of glycoproteomics in bladder cancer, the same group demonstrated cell surface expression of an ordinarily intracellular protein, homer homolog 3 (HOMER3), carrying short-chain O-glycans that are characteristic of membrane proteins ( 134 ). They further reported that under glucose deprivation and hypoxic conditions, HOMER3 contributed to the tumor cell’s invasive capacity.…”
Section: Hypoxia-driven Tumor Plasticity and Heterogeneity Incite Imm...mentioning
confidence: 99%
“…Of interest, cell-surface expression of this protein was associated with significantly worse survival in MIBC patients. Furthermore, while HOMER3 expression was not cancer-specific, STn and HOMER3 did not co-express in healthy tissue, suggesting that HOMER3-STn could be a tumor-specific biomarker that can be used to target the more aggressive cancer cell populations residing in the hypoxic TME ( 134 ). Similarly, some cancer-specific glycoconjugates, like N-glycolyl (NeuGc) GM3 gangliosides, are promising therapeutic targets, as their increased expression is characteristic in tumors and almost not present in healthy human tissues ( 135 ).…”
Section: Hypoxia-driven Tumor Plasticity and Heterogeneity Incite Imm...mentioning
confidence: 99%
“…Several tumour microenvironmental factors have been suggested to be upstream of glycan-associated phenotypic changes, including variations in oxygen [ 11 ], nutrients [ 24 ], and inflammatory cytokines levels [ 25 ]. The underlying structural alterations contribute to all accepted cancer hallmarks [ 9 ], highlighting the critical functional implications of glycans in cancer cells behaviour and fate [ 11 , 26 , 27 ], with considerable negative impact in clinical outcomes [ 10 , 28 , 29 ]. The most well-known glycome alterations result from premature stop in protein O -GalNAc glycosylation (occurring in Ser/Thr residues of proteins), yielding immature glycans, such as the Tn, sialyl-Tn (STn) and T antigens, rather than more extended and complex glycosidic chains.…”
Section: Cancer Associated Glycosylationmentioning
confidence: 99%
“…The sialylated Tn antigen, or sialyl-Tn (STn), is also frequently expressed in tumour tissues, including breast, gastrointestinal, lung, prostate, oesophagus, and bladder cancers [ 43 ]. It modulates key aspects of cancer progression, being an independent predictor of poor prognosis [ 14 , 29 , 43 ] frequently found in glycoproteins intimately linked to cancer aggressiveness [ 10 , 27 ]. Numerous reports describe STn as a driver of decreased cell adhesion [ 11 , 44 ], increased migratory and invasive [ 11 , 45 ] capacity of tumour cells, and decreased chemotherapy-induced apoptosis [ 46 ].…”
Section: Cancer Associated Glycosylationmentioning
confidence: 99%
See 1 more Smart Citation